Benefits of 3D Rotational DSA Compared with 2D DSA in the Evaluation of Intracranial Aneurysm - Wong, S.C.; Nawawi, O.; Ramli, N.; Abd Kadir, K.A. (Elsevier, 2012)
Rationale and Objectives: The aim of this study was to compare conventional two-dimensional (2D) digital subtraction angiography (DSA) with three-dimensional (3D) rotational DSA in the investigation of intracranial aneurysm in terms of detection, size measurement, neck diameter, neck delineation, and relationship with surrounding vessels. A further aim was to compare radiation dose, contrast volume, and procedural time between the two protocols. Materials and Methods: Thirty-five patients who presented with subarachnoid bleeds on computed tomography and were suspected of having intracranial aneurysms underwent conventional 2D DSA followed by 3D DSA. The 3D digital subtraction angiographic images were displayed as surface shaded display images. Aneurysm detection, sac size, neck diameter, neck delineation, and relationship of aneurysm to the surrounding vessels analyzed from the two protocols were compared. Radiation dose, contrast volume, and procedural time for both examinations were also compared. Results: Three-dimensional DSA detected 44 aneurysms in 31 patients, with negative findings seen in four patients. A false-negative detection rate of 6.8 (three of 44) for 2D DSA was noted. There was no significant difference in aneurysm size between 3D and 2D DSA. The sizes of aneurysm necks were found to be significantly larger in 3D DSA than on 2D DSA. The aneurysm neck and relationship to surrounding vessels were significantly better demonstrated on 3D DSA than on 2D DSA. Radiation dose (entrance surface dose), contrast use, and procedural time with 3D DSA were significantly less than with 2D DSA. Conclusions: Three-dimensional DSA improves the detection and delineation of intracranial aneurysms, with lower radiation dose, less contrast use, and shorter procedural time compared to 2D DSA. The size of the aneurysm neck on 3D DSA tended to be larger than on 2D DSA.